Avian-centric design - Abdul Shukor, Shureen Faris (Universiti Putra Malaysia Press, 2015)
Modern society has placed great faith in scientific research. Around the world thousands of scientists, inventors, and also designers are working to try to achieve a clear understanding of the conditions we live in and the universe that surrounds us. Nature has been a source of inspiration to many people. One of the best inspirations is the bird. Try browsing the internet under ‘bird inspired design’ and thousands of images will be scrolled out which display fashions, aircraft, furniture, shoes, jewelry, movies, fabrics, ballet dances, electronic games and many more.